O centro de Maceió: as referências de um patrimônio edificado - Carreiro, Larissa Santos (2017)
It is in the process of conception and construction of the city that references are created, which, in a historical neighborhood such as the Center of the city of Maceió, are sometimes confused with "goods that deserve to be preserved for their historical or artistic value", that is, with the equity. But, although it is a historic neighborhood, which has elements chosen as patrimony through its streets, to what extent can the Center be recognized as a patrimony? In order to answer these questions, these references will be approached in three different ways: first, from the revision of documentary collection based on books that deal with the beginning of the formation of the city, reports and postcards elaborated in the first decades of the twentieth century; after that, from the author's immersion in the Center of the city, visits through which the environment could be perceived, including the use of the senses for its understanding, as well as the election of its own references; and finally, through interviews with the passers-by in the neighborhood, with questions that promote a clash between all the references already identified. From this conflict, the idea is to reflect on the path that goes from the election of the value that should be attributed to a good by the responsible organs, until the receipt of this information by the population. After all, what lies between the lines that describe the official idea of the patrimony?